The natural rate of interest I: Theory - Philipp Johann König; Dmitry Chervyakov (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
The term natural (or neutral) real interest rate refers to the equilibrium value of the real interest rate. As this equilibrium is usually conceived as a situation where inflationary or deflationary pressures have abated, the natural real interest rate is a key concept for central banks seeking to stabilize the general price level or targeting the rate of inflation. The present roundup provides a brief historical review of this concept and explains the relevance of the natural real rate for monetary policy analysis.
Keywords: 330